Ciberviolencia en Relaciones de Pareja. - Bedón Casañas, Scarlett Sarahi (2025)
Cyber-violence in couples' relationships is defined as any form of aggression, control or harassment exercised through digital environments towards the couple. The main objective of this study was to characterise cyber-violence in couples' relationships. In this context, the methodology employed was a bibliographic and descriptive typology. Twenty scientific articles published between 2016 and 2025 were selected from databases such as: Google Scholar, Scopus, Dialnet, Web of Science, PubMed, SciELO, Medigraphic and Redalyc. The methodological quality of the selected articles was validated using the CRF-QS (Critical Review Form- Quantitative Studies) instrument, which comprises parameters that studies must meet to make a significant contribution to research. The results indicate that cyberaggressive behaviours in couples may be caused by various factors. Most people in romantic relationships engage in these cyberaggressive behaviours through mutual control and monitoring of their social networks, which has a significant social impact in the digital era as these practices of controlling one's partner online can have psychological effects on the victims.